MYCOBACTERIUM TUBERCULOSIS STRAIN H37RV INFECTION TOWARDS MATRIX METALLOPROTEINASE (MMP)-2 IN BRAIN - Hartono, Kevin; Adi, Prasetyo; Hidayati, Dwi Yuni Nur (Malang Neurology Journal, 2017)
Background. Tuberculous infection in brain can cause microglia to secrete inflammatory factors like Tumor Necrosis Factor alpha (TNF-α) and Interleukin 1 beta (IL-1β) which will be shown as body immune respons. Those inflammatory factors eventually can trigger microglia to secrete Matrix Metalloproteinase-2 (MMP-2) which will regenerate necrotic or apoptosis cells because of inflammation process. MMP-2 has been proven to have important role in brain tuberculous infection.Objective. To ascertain MMP-2 expression in mus musculus brain tissue with no infection, infection for 8 weeks, and infection for 16 weeks.Methods. This research used semiquantitative method to compare MMP-2 expression in 3 samples group. Observation of MMP-2 expression in mus musculus brain tissue were made by using immunohistochemistry colouration method which then would be observed in microscope with 400x magnification. Brain cell which express MMP-2 will become brown in cell nucleus, cytoplasm, and wall.Results. The result which had be obtained was overtime reduction of MMP-2 expression.Conclusion. MMP-2 expression didn’t decrease after 8 weeks time of infection.